Hydroxyapatite and Titania (HA-TiO2) powder mixed EDM for surface modification. - Razuki, Muhamad Afham (IRC, 2020)
Titanium dioxide (TiO2) is remarkable in biomedical field since its applications by surface modifications on metallic implant can prevent release of metal ions after long exposure to body fluids. Its combinations with hydroxyapatite powder can further enhance the biocompatibility as well as mechanical properties of implants. In this study we aimed to apply surface modification on stainless steel by powder mixed EDM using HA and TiO2 powder. It was found that material removal rate for the experiments conducted was higher than its respective electrode wear rate which indicate proper EDM as well as surface modification were successfully done. However, further analysis is required to determine the uncertainties of the surface modifications like its surface topography, surface roughness as well as elements and oxide compounds deposited.